2019
DOI: 10.3389/fimmu.2018.03139
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Staphylococcal Immune Evasion Protein Sbi as a Novel Vaccine Adjuvant

Abstract: Co-ligation of the B cell antigen receptor with complement receptor 2 on B-cells via a C3d-opsonised antigen complex significantly lowers the threshold required for B cell activation. Consequently, fusions of antigens with C3d polymers have shown great potential in vaccine design. However, these linear arrays of C3d multimers do not mimic the natural opsonisation of antigens with C3d. Here we investigate the potential of using the unique complement activating characteristics of Staphylococcal immune-evasion pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(88 reference statements)
0
12
0
Order By: Relevance
“… S. aureus commands numerous means to evade host complement-mediated damage ( 8 , 10 ). On its surface, this pathogen expresses protein A (SpA) and the secreted staphylococcal binder of IgG (Sbi), which bind to the Fc region of IgG and block C1q-dependent complement activation via the classical pathway ( 15 17 , 18 , 59 ). Furthermore, S. aureus staphylokinase cleaves the proenzyme plasminogen into active plasmin, which in turn inactivates C3 and C3b, and also cleaves IgG and extracellular matrix components to inhibit the classical complement pathway ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“… S. aureus commands numerous means to evade host complement-mediated damage ( 8 , 10 ). On its surface, this pathogen expresses protein A (SpA) and the secreted staphylococcal binder of IgG (Sbi), which bind to the Fc region of IgG and block C1q-dependent complement activation via the classical pathway ( 15 17 , 18 , 59 ). Furthermore, S. aureus staphylokinase cleaves the proenzyme plasminogen into active plasmin, which in turn inactivates C3 and C3b, and also cleaves IgG and extracellular matrix components to inhibit the classical complement pathway ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the circulating C3a anaphylatoxin is involved in inducing inflammatory immune responses, C3b (reported (1) normal plasma concentration:~210 ng mL -1 but levels are markedly higher on infection and under certain disease conditions although its short half-life (< 2 min) makes accurate measurements difficult) facilitates opsonophagocytosis and clearance of immune complexes through thioester-mediated opsonisation of primary amine-or hydroxyl-containing antigenic and self surfaces. Attachment of multiple copies of C3b and its breakdown products to antigenic surfaces in this way can result in C3d-complement receptor 2 (CR2/CD21) and antigen-B cell receptor (BCR) co-ligation which generates co-stimulatory signals for B cell activation in a C3d copy-dependent manner (2,3) and has been widely explored in vaccine design (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Intriguingly, a secondary binding mode for Sbi-IV on the convex surface of C3d revealed previously through X-ray crystallographic, NMR chemical shift perturbation ( 16 ) and SAXS analyses ( 26 ), is located near the base or hinge region of the swapped C3d 17C α1 helix, close to cysteine C17. It is at this position, between helices α1 and α2, where Sbi-IV helix α1 forms interactions with the thioester cysteine C17/1010 and surrounding residues S15/1008 and Q20/1013 of C3d [( Supplementary Figure S2 ( 17 )].…”
Section: Discussionmentioning
confidence: 70%
“…In addition to two N-terminal domains that bind the Fc region of IgG in a fashion similar to that of protein A (domains I and II) ( 25 ), we have previously shown that Sbi domains III and IV interact with complement proteins, whereby Sbi-IV binds to C3 fragments by interacting with the acidic residue-lined concave face of monomeric C3d ( 16 ), and in combination with Sbi domain III, activates the alternative complement pathway. We have recently shown that this property of Sbi can be harnessed as a vaccine adjuvant that promotes the opsonisation of antigens with a ‘natural’ coat of C3 breakdown products ( 26 ) via AP activation-mediated consumptive cleavage of C3 ( 22 ).…”
Section: Introductionmentioning
confidence: 99%